Mandatory Volunteer Work as Fair Reciprocity for Unemployment and Social Benefits? - Lex Veldboer; Reinout Kleinhans; Maarten van Ham (Institute for the Study of Labor (IZA), 2015)
Modern welfare policies are increasingly based on notions of reciprocity. Citizens on welfare benefits have to do something in return, e.g. volunteer work. Notwithstanding general public support, social philosophers have been critical on 'mandatory' activities in community programmes. So far, the participants themselves have scarcely been asked about the (un)fairness of 'mandatory volunteering'. This small exploratory study aims to reveal the perceptions of female participants in mandatory volunteering programmes and to formulate directions for further research. We analyse how in Rotterdam the transition from labour market re-integration policies to a mandatory reciprocity approach is viewed by long-term unemployed women who were already volunteering. Surprisingly, they claim that the new approach better recognises their contribution to 'society'. They also view the policy as necessary and fair to other benefit claimants who are perceived to lack any motivation to give something back to society. An agenda for further research is presented.
Keywords: J24; J28; J64; 330; social justice; welfare policies; gender; unemployment; reciprocity; volunteering; social benefits; austerity; Rotterdam